Provenance of exhalites associated with the Lemarchant volcanogenic massive sulphide (VMS) deposit, central Newfoundland, Canada:insights from Nd isotopes and lithogeochemistry - Lode, Stefanie; Piercey, Stephen J.; Cloutier, Jonathan (Journal of the Geological Society, 2017)
Neodymium isotope data on exhalites and tuffs from the Cambrian Lemarchant volcanogenic massive sulphide (VMS) deposit provide insights into the tectonic environment of the Tally Pond group, Canada. New data from exhalites from the Lemarchant area show evolved values of εNd513 = 6.0 to 1.8, whereas the associated volcanic rocks have εNd513 of +0.4 to +1.4. The Lemarchant exhalite εNd compositions overlap the underlying Ganderian Neoproterozoic Sandy Brook Group (εNdt = 6.5 to 1.9) and Crippleback Intrusive Suite (εNdt = 5.9 to 5.2). The evolved Nd isotopic signatures suggest that the volcanic rocks of the Tally Pond group were formed upon Ganderian arc basement, which itself was possibly built upon, or proximal to, the Gondwanan Amazonian margin. Erosion of older crustal material and Tally Pond group volcanic rocks, together with coeval eruption of the volcanic rocks, released Nd-rich detritus into the water column. Uptake of eroded detrital and scavenged Nd resulted in mixed Nd sources (juvenile and evolved), which are archived in the exhalites. The results of this study are of significance not only for occurrences of exhalites within the Tally Pond group, but also have exploration implications for VMS districts globally.